Calcium Sulfate Scale Formation in Nucleate Pool Boiling at Atmospheric Pressure (Chemical Engineering Research Bulletin, 2008)
Calcium sulfate scale formation, adherence and structure under pool boiling conditions were studied for a variety of surface materials and additives. Disc and ring type deposits were formed depending on conditions and can be explained in terms of accepted models. Nucleation of scale and scale structure depended on conditions with gold providing the most favorable nucleation for scale, but its initial deposition rate was very little more than for other surfaces. Additives had some effect on initial deposition rates but a more important effect on adhesion. Polyphosphate increased adhesion while starch decreased it. Taborek et al previously noted the importance of adhesion in regard to long term heat transfer under industrial conditions. A starch additive and a smooth gold surface lost scale readily which gave short term fluctuations and implied a constant and good long term average heat transfer coefficient.Chemical Engineering Research Bulletin 11 (2007) 101